Ghana : Selected Issues. (IMF Staff Country Reports; Country Report, 2003)
This Selected Issues paper reviews trends in GDP and their impact on poverty reduction in Ghana. It highlights structural constraints that are believed to have affected output growth, along with potential sources of increases in output in future years. The paper analyzes trends in the main production sectors, and presents an assessment of the underlying determinants of growth and poverty reduction. It also explores the key elements of the authorities' strategy to raise GDP per capita growth as set out in the Ghana Poverty Reduction Strategy.